The Importance of reading in early childhood education (REMUNOM, 2024)
Children's literature inserted into a teaching-learning process can facilitate the child's development and knowledge, since the student's information and experiences will be built up in a playful and enjoyable way. Based on this premise, the aim of this article was to briefly present the benefits of reading and the narratives of literature in early childhood education, emphasizing the importance of reading stories. The study presented is qualitative in nature and is a literature review, with the aim of gathering information on the importance of reading practice in early childhood education and summarizing it in a document, mainly for didactic use. From the observations and research carried out, it was possible to see that the relationship with reading from an early age guarantees the development and growth of literate individuals, because as well as developing good reading and improving cognitive skills, it also influences the interpretation of the world and our acquisition of knowledge. It also has positive impacts such as developing concentration, memory, reasoning and comprehension, stimulating oral language and expanding creative capacity.